Implementation of Distance Learning Activities Processes During the Covid-19 Pandemic at SDN 1 Selajambe - Yuthika, Ghaida (Devotion : Journal of Research and Community Service, 2022)
Social distancing is urgently applied to break the chain of transmission of the Covid-19 outbreak so that all work and education activities are conducted at home or often called WFH (Work From Home). The research technique used here was descriptive qualitative research, intending to understand the process of implementing learning activities during distance learning as well as the supporting and inhibiting variables for distance learning implementation at SDN 1 Selajambe. Observations in this study were carried out on the Principal, and Class 4 Teacher of SD Negeri 1 Salajambe. The data collection techniques were observation and interviews. The result shows that the process of learning activities during the pandemic conducted through online learning techniques. Teachers can use various applications such as the Ruang Guru Application, Google Classroom, Zoom, Google Docs, Google Form, or WhatsApp groups. Apart from online, there are also offline activities by forming study groups.